2019
DOI: 10.1039/c9ra06255f
|View full text |Cite
|
Sign up to set email alerts
|

Fe3O4/granular activated carbon as an efficient three-dimensional electrode to enhance the microbial electrosynthesis of acetate from CO2

Abstract: Microbial electrosynthesis (MES) allows the transformation of CO2 into value-added products by coupling with renewable energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…For example, Zhu and co-workers have also reported a concentration-dependent effect on MES upon metal (iron) oxide impregnation on activated carbon biocathodes. 6 Specifically, acetate production and electron recovery were shown to increase with increasing amounts of Fe3O4, compared to control electrodes, reaching a maximum when 38% Fe3O4 was added, whereas a decrease in electron recovery and acetate production was recorded when 50% Fe3O4 was added on the electrode. Similarly, the microbial community composition revealed a concentration-dependent effect of Fe3O4 addition, with Arcobacter and Acetobacterium exhibiting the highest abundance in the presence of 38% Fe3O4, and this was correlated to improved acetate production by the authors.…”
Section: Improved Product Formation With Added Nickel Reveals the Rol...mentioning
confidence: 89%
See 3 more Smart Citations
“…For example, Zhu and co-workers have also reported a concentration-dependent effect on MES upon metal (iron) oxide impregnation on activated carbon biocathodes. 6 Specifically, acetate production and electron recovery were shown to increase with increasing amounts of Fe3O4, compared to control electrodes, reaching a maximum when 38% Fe3O4 was added, whereas a decrease in electron recovery and acetate production was recorded when 50% Fe3O4 was added on the electrode. Similarly, the microbial community composition revealed a concentration-dependent effect of Fe3O4 addition, with Arcobacter and Acetobacterium exhibiting the highest abundance in the presence of 38% Fe3O4, and this was correlated to improved acetate production by the authors.…”
Section: Improved Product Formation With Added Nickel Reveals the Rol...mentioning
confidence: 89%
“…Increased surface area and roughness for improved biofilm coverage and attachment 5,7 Increased electron conductivity and decreased charge-transfer resistance for improved electron transfer to biofilm-forming microorganisms 5 -7,11 Electrocatalyst Electrocatalytic production by the metal catalyst of electron donors (e.g., H2) that can be oxidized by microorganisms in the biofilm or in the planktonic phase 8,9 Trace element Increased availability of a certain trace element (i.e., added metal) that can improve microbial growth (in case the concentration was limiting) 12,13 or alter the enzymatic pathways 14 and/or microbial community composition 15,16 Toxic compound Inhibition of microbial growth or altered microbial community composition via inhibition of metal-sensitive taxa due to high metal concentration 17,18 While both the indirect (e.g., surface properties) and direct effects (e.g., H2 production) of nickel nanostructures on MES are well known and described separately, the combination of these effects on MES has been overlooked during previous studies. For example, during studies on the effect of metals on the surface and electron transfer properties of the electrode, [5][6][7] the authors did not report abiotic testing of the synthesized cathodes, which would have revealed whether H2 production was enhanced due to metal addition, thus leading to improved acetate production by the microorganisms. Similarly, during studies on the catalytic activity of metals and its effect on MES, 8 the authors correlated the improved acetate production solely to the H2 production, without reporting the effect of the metal on the surface properties of the electrode.…”
Section: Role Of Metal Explanation Of Interaction Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…Common strategies include increasing the surface area of the electrode or modifying the surface to promote attachment. Electrode architecture, such as nanowires [41] or fluidized granular active carbon (GAC) 3D electrodes, [42,43] provide a massive surface area to enable high bacterial loadings. Functionalization of the electrode with charged polymers can also improve bacterial attachment through electrostatic attraction, [44] whereas amide [45] or quinoid [46] functional groups may improve electron transfer.…”
Section: Combining Electrochemical Systems With Living Cellsmentioning
confidence: 99%